Spatiotemporal variations, assembly processes, and co-occurrence patterns of particle-attached and free-living bacteria in a large drinking water reservoir in China - Yu, Bobing; Xie, Guijuan; Shen, Zhen; Shao, Keqiang; Tang, Xiangming (Frontiers in Microbiology, 2023)
Particle-attached (PA) and Free-living (FL) bacterial communities are sensitive to pollutant concentrations and play an essential role in biogeochemical processes and water quality maintenance in aquatic ecosystems. However, the spatiotemporal variations, assembly processes, co-occurrence patterns, and environmental interactions of PA and FL bacteria in drinking water reservoirs remain as-yet-unexplored. To bridge this gap, we collected samples from 10 sites across four seasons in Lake Tianmu, a large drinking water reservoir in China. Analysis of 16S rRNA gene libraries demonstrated spatiotemporal variation in bacterial diversity and identified differences in bacterial community composition (BCC) between PA and FL lifestyles. Capacity for nitrogen respiration, nitrogen fixation, and nitrate denitrification were enriched in the PA lifestyle, while photosynthesis, methylotrophy and methanol oxidation were enriched in the FL lifestyle. Deterministic processes, including interspecies interactions and environmental filtration, dominated the assembly of both PA and FL bacterial communities. The influence of environmental filtration on the FL community was stronger than on the PA community, indicating that bacteria in the FL lifestyle were more sensitive to environmental variation. Co-occurrence patterns and keystone taxa differed between PA and FL lifestyles. The ecological functions of keystone taxa in the PA lifestyle were associated with supply and recycling of nutrients, while those in FL were associated degradation of complex pollutants. PA communities were more stable than FL communities in the face of changing environmental conditions. Nutrients (e.g., TDN and NO3-) and abiotic and biotic factors (e.g., WT and Chl-a) exerted positive and negative effects, respectively, on co-occurrence networks of both lifestyles. These results improve our understanding of assembly processes, co-occurrence patterns, and environmental interactions within PA and FL communities in a drinking water reservoir.